Exploring the Intersection of Youth Development, Physical Education, Teacher Education, and Social Justice - Cory Elijah Dixon (Youth, 2025)
There are few conceptual frameworks or models related to educators’ competencies at the intersection of social justice; youth development; and physical education, activity, or sport content and pedagogy. The purpose of this multiple case study was to examine how the racialized and pedagogical experiences of individuals teaching physical education contribute to understanding the integration of social justice principles in youth development contexts through sport and physical activity. This study involved the within-case and cross-case analyses of two main cases: preservice teachers and graduate teaching assistants teaching physical education in a youth development context. The preservice teacher and the graduate teaching assistant within-case analysis each resulted in two complementary themes (four total). The cross-case analysis resulted in three total themes. Together, these seven themes are conceptualized into three categories: (1) assumptions prior to teaching, (2) emergent just teaching, and (3) considering race. While training all future professionals for equitable and justice-oriented teaching is key, we cannot ignore the glaring reality that many individuals with more culturally diverse backgrounds are predisposed to embodying such orientations. Findings reinforce the importance of preparing (and recruiting) educators who not only have pedagogical skills but who can also teach for justice.